Coalition formation for throughput enhancement in cognitive radio wireless networks - Tahir, Mohammad; Habaebi, Mohamed Hadi; Islam, Md Rafiqul (Asian Research Publishing Network (ARPN), 2015)
Recently there have been numerous studies exploring the benefits of the coalition formation in a cognitive radio network and it has been shown that coalition formation tends to improve the performance of cognitive radio. In this paper we use the concepts from matching theory, specifically we use Gale-Shapley algorithm, to form the coalition among cognitive radio user for collaborative spectrum sensing under target detection probability constraint. In the proposed model we modify Gale-Shapley algorithm for the cognitive radio users to form coalitions of varying size to improve their individual gains (.e.g. throughput and probability of false alarm). We show using simulations that using the modified gale shapely algorithm for coalition formation yields significant gains in term of reduced false alarm probability and increased throughput per cognitive radio user as compared to non-cooperative scenario.